P03.04 Primary CNS lymphoma of the corpus callosum: presentation and neurocognitive prognosis. Study of a monocentric cohort of 27 patients. (9th September 2021) - Nilles, C; Delgadillo, D; Martin Duverneuil, N; Mokhtari, K; Mathon, B; Hoang-Xuan, K; Duran-Pena, A; Morales, A; Houillier, C
Abstract: BACKGROUND: The corpus callosum (CC) is frequently involved in primary central nervous system lymphomas (PCNSL). The aim of our study was to describe the impact of these lesions on neurocognition of patients presenting with PCNSL of the CC (PCNSL-CC) and their post-therapeutic evolution. MATERIAL AND METHODS: This is a retrospective single-center study. Patients newly diagnosed at Pitié Salpêtrière Hospital from (1999–2018) were included in this study according to the following criteria: age >18, immunocompetent patient, pathological confirmation (Diffuse Large B cell lymphoma) and CC as main location of the tumor on MRI. Clinical, neuroradiological and neuropsychological data of the patients were collected. In addition, prognostic factors for the neurocognitive outcome of the patients were investigated. RESULTS: 27 patients were included (median age: 67 years, median KPS: 70). At the time of diagnosis, 74% of patients had cognitive impairment and 59% of patients had balance disorders. The cognitive functions most frequently affected were memory and executive functions. Tumor lesions in the CC had a median maximum diameter of 5 cm with a so called "butterfly pattern" in 92% of cases. All patients received a high dose methotrexate based polychemotherapy, including one with radiation therapy, and 67% of patients achieved a complete remission (CR). Median PFS and OS were 33.3 months and 177.9 months respectively. With a median follow-up of 48 months (range 6–156), despite CR, there were still abnormal values in 17% of patients on overall efficiency, 17–55% of patients on executive function tests, 45–55% of patients on memory tests. No significant impaired values were found for visuo-spatial and language tests. Splenial location and age ≥ 60 years were significantly associated with worse episodic memory scores throughout the follow-up. CONCLUSION: PCNSL-CC are associated with frequent cognitive dysfunctions, especially memory impairment, which may recover only partially despite CR, that warrant specific rehabilitation. Older age (≥ 60) and splenial location have worse neurocognition outcome.